Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

Evaluating the suitability of large-scale datasets to estimate nitrogen loads and yields across different spatial scales - Andrés Felipe Suárez-Castro; Dale M. Robertson; Bernhard Lehner; Marcelo L. de Souza; Michael Kittridge; David A. Saad; Simon Linke; Rich W. McDowell; Mohammad Hassan Ranjbar; Olivier Ausseil; David P. Hamilton (Water Research, 2025)

Where should hydrology go? An early-career perspective on the next IAHS Scientific Decade: 2023–2032 - Theresa C. van Hateren; Harro J. Jongen; Hadeel Al-Zawaidah; Joris G.W. Beemster; Judith Boekee; Linda Bogerd; Sijia Gao; Christin Kannen; Ilja van Meerveld; Sjoukje I. de Lange; Felicia Linke; Rose B. Pinto; et al. (Hydrological Sciences Journal, 2023)

Peripartum cardiomyopathy: a global effort to find the cause and cure for the rare and little understood disease - Amy Li; K. Campbell; S. Lal; Y. Ge; A. Keogh; P. S. Macdonald; P. Lau; John Lai; W. A. Linke; J. Van der Velden; A. Field; B. Martinac; et al. (Biophysical Reviews, 2022)
In this review, we present our current understanding of peripartum cardiomyopathy (PPCM) based on reports of the incidence, diagnosis and current treatment options. We summarise opinions on whether PPCM is triggered by vascular and/or hormonal causes and examine the influence of comorbidities such as preeclampsia. Two articles published in 2021 strongly support the hypothesis that PPCM may be a familial disease. Using large cohorts of PPCM patients, they summarised the available genomic DNA sequence data that are expressed in human cardiomyocytes. While PPCM is considered a disease predominately affecting the left ventricle, there are data to suggest that some cases also involve right ventricular failure. Finally, we conclude that there is sufficient evidence to warrant an RNAseq investigation and that this would be most informative if performed at the cardiomyocytes level rather than analysing genomic DNA from the peripheral circulation. Given the rarity of PPCM, the combined resources of international human heart tissue biobanks have assembled 30 ventricular tissue samples from PPCM patients, and we are actively seeking to enlarge this patient base by collaborating with human heart tissue banks and research laboratories who would like to join this endeavour.

Do people accurately report droughts? Comparison of instrument-measured and national survey data in Kenya - Andrew M. Linke; Frank D. W. Witmer; John O’Loughlin (Climatic Change, 2020)

Correction to: The Sydney Heart Bank: improving translational research while eliminating or reducing the use of animal models of human heart disease - C. G. dos Remedios; S. P. Lal; A. Li; J. McNamara; A. Keogh; P. S. Macdonald; R. Cooke; E. Ehler; R. Knöll; S. B. Marston; J. Stelzer; H. Granzier; et al. (Biophysical Reviews, 2018)

The Sydney Heart Bank: improving translational research while eliminating or reducing the use of animal models of human heart disease - C. G. dos Remedios; S. P. Lal; A. Li; J. McNamara; A. Keogh; P. S. Macdonald; R. Cooke; E. Ehler; R. Knöll; S. B. Marston; J. Stelzer; H. Granzier; et al. (Biophysical Reviews, 2017)

Enhancing conservation of A ustralian freshwater ecosystems: identification of freshwater flagship fishes and relevant target audiences - Brendan C Ebner; David L Morgan; Adam Kerezsy; Scott Hardie; Stephen J Beatty; Jamie E Seymour; James A Donaldson; Simon Linke; Stirling Peverell; David Roberts; Thomas Espinoza; Nadine Marshall; et al. (Fish and Fisheries, 2016)
Flagship species, especially mammals and birds, are commonly used to increase awareness of conservation issues in marine and terrestrial ecosystems. However, flagship species oriented programs are often ad hoc with initiatives scarce in the freshwater context. Here, we aim to identify potential flagship candidates that would appeal to a broad cross section of society at a continental scale where freshwater ecosystems are under threat from human impacts. We identified 19 species from a list of 299 Australian freshwater fishes on the basis of body size, trophic guild and threatened species status assuming these characteristics of flagship species are transferable from previous work on terrestrial flagship species. We considered the potential of species to be of international appeal but focused mostly on eight relevant interest groups within Australia. This followed the rationale that public engagement with conservation issues in freshwater systems might be more effective if the link between fish species and the decisions people make were better understood, and we acknowledge the diverging interests of stakeholders. This scoping work contributes towards addressing the challenges of connecting societies to the principles of sharing water resources with ecosystems, and represents the first continental‐scale assessment of its kind.

Expression, localization, and regulation of the iron transporter LeIRT1 in tomato roots - A. Schikora; O. Thimm; B. Linke; T. J. Buckhout; M. Müller; W. Schmidt (Plant and Soil, 2006)

Enhanced resistance to Phytophthora infestans and Alternaria solani in leaves and tubers, respectively, of potato plants with decreased activity of the plastidic ATP/ADP transporter - Uwe Conrath; Christoph Linke; Wolfgang Jeblick; Peter Geigenberger; W. Paul Quick; H. Ekkehard Neuhaus (Planta, 2003)

Passive stiffness changes in soleus muscles from desmin knockout mice are not due to titin modifications - Anderson J.; Joumaa V.; Stevens L.; Neagoe C.; Li Z.; Mounier Y.; Linke W.; Goubel F. (Pflügers Archiv - European Journal of Physiology, 2002)

Stoffwechselprodukte von Mikroorganismen - W. -D. Linke; A. Crueger; H. Diekmann (Archives of Microbiology, 1972)